2002
DOI: 10.1034/j.1600-0412.2002.810309.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during pregnancy: comparison of self‐reports and cotinine levels in 496 women

Abstract: If the true facts about exposure to tobacco smoke are not revealed, a number of women who might benefit from information and support at the antenatal clinic will miss the opportunity of such assistance, resulting in increased risks for both the woman and her fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 18 publications
9
81
1
Order By: Relevance
“…[53][54][55] Exposure can be assessed with standard questionnaires on smoking, and results can be validated with measurements of serum cotinine levels for a randomly selected group of participants. 56 The second source is breastfeeding. Because of its lipophilic nature, nicotine is readily found in human milk, at concentrations that can be 3 times as high as those in the blood; because nicotine is absorbed orally, the infant of a smoking mother is exposed to significant amounts of nicotine if breastfed.…”
Section: Comprehensive Assessment Of Tobacco Exposurementioning
confidence: 99%
“…[53][54][55] Exposure can be assessed with standard questionnaires on smoking, and results can be validated with measurements of serum cotinine levels for a randomly selected group of participants. 56 The second source is breastfeeding. Because of its lipophilic nature, nicotine is readily found in human milk, at concentrations that can be 3 times as high as those in the blood; because nicotine is absorbed orally, the infant of a smoking mother is exposed to significant amounts of nicotine if breastfed.…”
Section: Comprehensive Assessment Of Tobacco Exposurementioning
confidence: 99%
“…[22][23][24][25][26] Studies conducted in Australia and elsewhere using biochemical testing to validate self-reporting of smoking status have reported that between 6% and 39% of smoking women do not disclose their smoking status. [27][28][29][30][31] Greater levels of non-disclosure are found in women who are older, married and have higher socioeconomic status. 23,26,27 As a result, the true prevalence of maternal smoking is likely to be under-estimated and opportunities for smoking cessation interventions could be missed.…”
mentioning
confidence: 99%
“…A concentration of 15 ng/mL in saliva or serum is a conservative cut point for detecting active smoking (2,3). Using cotinine to check smoking status, there is evidence that self-report is unreliable in specific populations where there is pressure not to admit smoking, such as patients with respiratory illness (4,5) or cancer (6) or pregnant women (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%